Separation of single component of EPA and DHA from fish oil using silver ion modified molecular sieve 13X under supercritical condition - Hao, Liu-Ping; Cao, Xue-Jun; Hur, Byung-Ki (Journal of industrial and engineering chemistry (Seoul, Korea), 2008)
The importance of polyunsaturated fatty acids (PUFAs) in human nutrition and disease prevention was demonstrated four decades ago. EPA and DHA are important PUFAs. Separation of EPA and DHA has been carried out under supercritical condition by using a silver ion modified molecular sieve 13X (MS13X). MS13X was modified by silver nitrate, and the modification reaction was optimized by stir model, the concentration of silver nitrate and temperature. It was found that the optimized reaction conditions are stirring with nitrogen bubbling, 0.1 mol/l silver nitrate and 20 °C in the dark. Results indicated that 1 g MS13X could be bound by 7.4 mg silver ion, namely 12.4% sodium of MS13X was exchanged. The modified MS13X (called SN13X) displays maximum adsorption capacity of EPA and DHA at 40 °C, with 37.4 mg/g and 24.2 mg/g, respectively. SN13X was packed in the column (20 cm × 1 cm) under supercritical fluid apparatus, and adsorption, washing and elution of EPA and DHA were carried out by gradient pressure. In this study, the purity of EPA and DHA were enhanced to 88.4% and 84.3% from 20.4% and 12.7%, with recovery of 45.8% and 39.2%, respectively.